Analysis of Photocopy Service Queue System in “Sustainable Photocopy” Using The FIFO Queue Method - Wira Yudha Nuswantoro; Erwan Adi Saputro; Mutiara Mei Susanti; Yekti Condro Winursito; Hafid Syaifullah (UNIPA PRESS, 2023)
Photocopying services are services that are always sought by students, students, teachers, lecturers, and even office people for the need to duplicate school assignments, theses, document files, etc.